The wife : a novel - Burke, Alafair (New York, N.Y. : Harper, an imprint of HarperCollinsPublishers, 2018)
Marrying an economics professor she met while catering an East Hampton dinner party, Angela finds her tragic past coming under scrutiny at the same time she is asked to defend her husband against wrongful accusations.
Keywords: Spouses -- Fiction; Married people -- Fiction; Suspense fiction; Suspense fiction